The Effect of Internal Audit Against Fraud Prevention: Case Study in PT. Asuransi Jasa Indonesia - Mochammad Taufik; Mirna Dianita (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
This study aims to determine the effect of internal audit on fraud prevention. The object of this research was conducted at PT Asuransi Jasa Indonesia.This type of research is quantitative research. The population in this study amounted to 30 people. The data collected is by distributing questionnaires with correlation data analysis, coefficient of determination, and hypothesis testing t. This study uses SPSS 22 tools for windows. that the implementation of internal audit at PT Asuransi Jasa Indonesia is good enough. In addition, the results of the correlation test indicate that the application of internal audit at PT. Indonesian Insurance Services are quite strong. Hypothesis test results also indicate that internal audit affects fraud prevention at PT Asuransi Jasa Indonesia (fraud).